Crime of Fraud (Pig Butchering Scam) Through Social Media in the Perspective of Islamic Criminal Law - Muhammad Syafriza Aqib; Sukiati (Warmadewa Press, 2024)
Along with the development of internet technology at this time which has a lot of positive impacts on its users, of course it also has a negative impact on the development of the internet. One of them is online fraud through social media that uses the pig butchering scam mode. Pig butchering scam is a fraud mode that has been rampant in Indonesia in recent years. This mode relies on social media to run the scam. The perpetrator will use a fake account and identity then offer fraudulent investments or freelance work with the lure of large profits that will be obtained at the beginning. This study aims to first understand the mode of criminal act of pig butchering scam applied in fraud through social media. Second, to find out the characteristics of the pig butchering scam crime. Third, to find out the legal action against the crime of pig butchering scam in the perspective of criminal law and Islamic criminal law. This study uses a normative juridical research method, as well as applying a case approach. Using the library research method, data collected based on documents that discuss the topic of pig butcheing scam from various literature. This study obtained the results that criminal acts with the pig butchering scam mode through social media are included in the category of criminal acts of fraud as regulated in Article 378 of the Criminal Code. So it can be concluded from the results of this study, namely the crime of pig butchering scam through social media, including criminal acts that can harm the victim materially or immaterially. Thus, it is hoped that there must be actions that prevent this act from occurring, with benefits such as increasing public knowledge about investment and increasing supervision of forms of investment in social media.